THE EFFECT OF BOND AGE, INTEREST RATE AND INFLATION RATE OF RETURN ON BONDS - Muhamad Ekhsan; Mochammad Fahlevi (KOMMAS: Jurnal Pengabdian Kepada Masyarakat, 2020)
Bonds selected investors as an investment instrument because it has a fixed return of interest or coupon and yield with a low level of risk. The formulation of the problem in this study is whether the life of the bond partial effect on government bond yields, whether the interest rate partially on government bond yields, whether inflation partial effect on government bond yields and whether the life of the bond, the interest rate and inflation influence simultaneously on government bond yields. The methodology used in this study is a quantitative research design. Sample of this research is of conventional government bonds listed on the Stock Exchange in 2018 period is determined using purposive sampling method. Data analysis method used in this research is the analysis of quantitative data to calculate and estimate quantitatively some independent variables on the dependent variable partially or silmultan. Results from these studies show that the partial term of the bonds does not significantly influence government bond yields, interest rates partially significant effect on government bond yields and partial inflation no significant effect on government bond yields. While simultaneously the life of the bonds, interest rates and inflation significantly influence government bond yields listed in BEI period of 2018. partial interest rate significantly influence the yields on government bonds and partial inflation no significant effect on government bond yields. While simultaneously the life of the bonds, interest rates and inflation significantly influence government bond yields listed in BEI period of 2018. partial interest rate significantly influence the yields on government bonds and partial inflation no significant effect on government bond yields. While simultaneously the life of the bonds, interest rates and inflation significantly influence government bond yields listed in BEI period of 2018.